ARTIFICIAL INTELLIGENCE: REVOLUTIONARY APPROACHES AND THE SECRETS OF EFFICIENCY IN FOREIGN LANGUAGE TEACHING - M.B. Mirzaraimova (Ta'lim innovatsiyasi va integratsiyasi, 2025)
This article investigates the transformative influence of Artificial Intelligence (AI) on foreign language pedagogy, focusing on its methodological innovations, adaptive learning  potential,  and  assessment  automation.  Through  the  integration  of  natural language  processing,  speech  recognition,  and  intelligent  tutoring  systems,  AI  has redefined  traditional  teaching  frameworks.  This  article  explores  how  AI  fosters personalized learning, enhances pronunciation, and promotes learner autonomy. The article  argues  that  AI  not  only  increases  efficiency  and  engagement  in  language learning but also contributes to the evolution of communicative competence in the digital era.